Effectiveness of Using The Storytelling Method With Paper Puppet Animation Prototypes to Improve Speaking Skills in UPT SPF State Elementary School 106172 Deli Serdang - Asmika, Suci; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
Based on the results of the researcher's observations, grade IV students of SPF UPT SD Negeri 106172 Tuntungan , During the Indonesian Language learning process, it is known that students' interest in storytelling activities is still low. This study aims to determine whether or not there is an influence of paper puppet media on speaking skills in Indonesian language subjects for class IV UPT SPF SD Negeri 106172 Tuntungan. This type of research is quantitative experimental research (Quasi Experiment Design), with the Nonequivalent Posttest-Only Control Group Designs approach, where in this study there are two groups, namely the experimental group and the control group, data collection techniques through tests. The population was taken from all students of UPT SPF SD Negeri 106172 Tuntungan , with samples taken from classes IV A and B as many as 40 people. The data validity test was validated by experts, while the data reliability test used the Alpha formula. The data analysis technique used the Liliefors formula. The results of this study showed the influence of paper puppet media on speaking skills in Indonesian language subjects for class IV UPT SPF SD Negeri 106172 Tuntungan. The results are based on the results of the "t-test" calculation, namely (15.49090) > (2.10092) which means that there is acceptance in (ha) and rejection (ho). From the posttest results obtained by class IV A (experiment) with an average value of 80.25 and the posttest results obtained by class IV B (control) with an average value of 64.25, this shows that the experimental class' speaking skill score is higher than the control class. So it can be concluded that there is an influence of paper puppet media on speaking skills in Indonesian Language subjects